Evaluating the use of PTSD Assessment Tools Within the U.S. Prison Setting: An Exploratory Analysis - Dulisse, Brandon C. (The prison journal, 2023)
The identification and treatment of post-traumatic stress disorder (PTSD) in carceral settings remain a fundamental concern for practitioners, policy-makers, and incarcerated persons (IPs) alike. In recent years, PTSD assessment tools designed for the general population have been adopted for use in prisons upon intake, sometimes side-by-side with other assessment tools. This study attempts to provide insight into how these tools are used for a majority of IPs within the United States. Based on results from six U.S. states and the federal prison system, we find that PTSD assessment would benefit from newer tools designed for the specific challenges in the prison environment.